Contraceptive use in Flanders (Belgium): A comparison between a general population sample and a Turkish ethnic minority sample. (August 2015) - Elaut, Els; Buysse, Ann; Caen, Maya; Vandamme, Joke; Vermeire, Katrien; T'Sjoen, Guy
Abstract Objectives To identify contraceptive profiles, and factors affecting these, among women of childbearing age, living in Flanders. Methods The prevalence of knowledge and use of the emergency contraceptive pill (ECP) and contraceptive use is assessed in two samples from the SEXPERT-survey 'Sexual health in Flanders': (i) a population-based sample (n = 724); and (ii) a probability sample of respondents of Turkish descent (n = 216). Results Knowledge, but not use, of the ECP is significantly lower among women from the ethnic minority sample, even after correction for income and educational background. A lower educational level is associated with less knowledge of the ECP in both samples. In the general population sample, 16% of sexually active women of childbearing age are at risk of an unplanned pregnancy, compared to 14% of their peers of Turkish origin. These rates are comparable, even after controlling for the different socio-economic status (income and educational level) in both samples. Conclusions Contraceptive profiles of sexually active women of Turkish descent residing in Flanders are mostly similar to those of their counterparts in the general population. Further research is required to develop strategies to improve ECP-knowledge among women with lower educational achievements.